2011 International Conference on Collaboration Technologies and Systems (CTS) 2011
DOI: 10.1109/cts.2011.5928688
|View full text |Cite
|
Sign up to set email alerts
|

A deceptive robot referee in a multiplayer gaming environment

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…A common pattern is that unless the behavior is very obviously deceptive, users tend to perceive being deceived as unintentional: an error on the side of the robot [23,28,32]. In a taxonomy of robot deception, Shim et al [27] associate physical deception with unintentional, and behavioral deception with intentional.…”
Section: Study 5: Implications Of Deception For Hrimentioning
confidence: 99%
See 2 more Smart Citations
“…A common pattern is that unless the behavior is very obviously deceptive, users tend to perceive being deceived as unintentional: an error on the side of the robot [23,28,32]. In a taxonomy of robot deception, Shim et al [27] associate physical deception with unintentional, and behavioral deception with intentional.…”
Section: Study 5: Implications Of Deception For Hrimentioning
confidence: 99%
“…And, if so, what implications does this have on how they perceive the robot? Literature on the ethics of deception cautions about a drop in trust [2,20], while work investigating games with cheating robots measures an increase in engagement [28,32]. We use these as part of our dependent measures in the study.…”
Section: Study 5: Implications Of Deception For Hrimentioning
confidence: 99%
See 1 more Smart Citation
“…Work at Yale University (Short, Hart, Vu, & Scassellati, 2010) illustrated increased engagement with a cheating robot in the context of a rock-paper-scissor game, demonstrating greater attribution of mental state to the robot by the human players when participants played against a cheating robot. At Carnegie Mellon University (Vazquez, May, Steinfeld, & Chen, 2011) a study showed an increase of user's engagement and enjoyment in a multi-player robotic game in the presence of a deceptive referee. By declaring false information to game players about how much players win or lose, they observed whether this behavior affects a human's general motivation and interest based on the frequency of winning, duration of playing, etc.…”
Section: Robot Deceptionmentioning
confidence: 99%
“…They proved greater attributions of mental state to the robot by the human players, when participants played against the cheating robots. At Carnegie Mellon University [17] a study showed an increase of user's engagement and enjoyment in a multi-player robotic game in the presence of a deceptive referee. By declaring false information to game players about how much players win or lose, they observed whether this behavior affects a human's general motivation and interest based on frequency of winning, duration of playing, and so on.…”
Section: Robot Deceptionmentioning
confidence: 99%